Does corporate social responsibility affect earnings management? Evidence from family firms - Eva López-González; Jennifer Martinez-Ferrero; Emma García-Meca (Revista de Contabilidad: Spanish Accounting Review, 2019)
The purpose of this paper is to shed light on the effect of corporate social responsibility performance on earnings management. We also examine the moderating role of family ownership on the association between earnings management and socially responsible performance. Based on an international sample of 6,442 firm-year observations from 2006 to 2014, we use several validated analysis and panel-data regression models. We find that social and environmental performance is positively related with earnings management; firms with a greater socially responsible performance show a higher discretionary behavior by promoting actions that mask the real financial and economic performance of the firm. However, we find that this positive relation is lower – moderated - in family-owned firms, mainly because of the fact that family firms show a greater socially responsible behavior aimed to preserve their socioemotional endowments and are negatively associated with earnings management practices.